Cost Calculation Using Full and Variable Costing in Sandal Cantikku - Dicky Sastra Wiguna (INCOME: Innovation of Economics and Management, 2022)
The cause of this dedication is to provide steering on calculating the cost of Manufacturing using the Full Method Costing and Variable Costing in Sandal Cantikku Domestic Industry. Companion on this dedication is Sandal Cantikku Domestic Industry in the city of Sidoarjo. The coaching is executed out use of lecture approach, tutorial and discussions held in one day. It is hoped that with this steerage, Sandal Cantikku Domestic Industry are capable of use accounting in this situation port calculations manufacturing and supplying inside the shape of a main production fee record to be taken into consideration in selling charge determination, profit calculation, and different accounting facts. With rate calculation manufacturing is expected to decide accurate selling costs, correct profits calculations, and accounting statictics true enough